Cyclin E1 deregulation occurs early in secretory cell transformation to promote formation of fallopian tube derived high-grade serous ovarian cancers - Karst, Alison M. (Cancer Res, 2013)
Fallopian tube is now generally considered the dominant site of origin for high-grade serous ovarian carcinoma. However, the molecular pathogenesis of fallopian tube-derived serous carcinomas are poorly understood and there are few experimental studies examining the transformation of human fallopian tube cells. Prompted by recent genomic analyses that identified Cyclin E1 (CCNE1) gene amplification as a candidate oncogenic driver in serous ovarian carcinoma, we evaluated the functional role of CCNE1 in serous carcinogenesis. CCNE1 was expressed in early and late stage human tumor samples. In primary human fallopian tube secretory epithelial cells, CCNE1 expression imparted malignant characteristics to untransformed cells if p53 was compromised, promoting an accumulation of DNA damage and altered transcription of DNA damage response genes related to DNA replication stress. Together our findings corroborate the hypothesis that Cyclin E1 dysregulation acts to drive malignant transformation in fallopian tube secretory cells that are the site of origin of serous ovarian carcinomas.